Talent identification: line managers’ perceptions of their own requirements as talent spotters - Golik, Mariela; Blanco, María Rita (Revista Venezolana de Gerencia, 2024)
Identification is a key step in the organizational talent management process. Even though evaluating potential through an objective approach, integrating multiple methods, is recommended, many organizations rely upon line manager nominations as their main sources of identification. Given their central role, this study analyses the line managers’ attributes required to carry out an effective talent identification process. This qualitative study was drawn upon social cognition (social psychology framework) and talent identification literature with a sample of 20 managers, belonging to a multinational of Argentine origin, who described their experiences and requirements as talent spotters through semi-structured interviews. Results suggest that observation skills, listening and communication skills, cognitive skills, intuition, empathy, identification as part of the managerial role, low aversion to risk, vocation, predisposition to learn, resilience, and commitment are important attributes in the identification process. The present study provides a map of the talent spotter´s attributes that are necessary to assess employees´ potential.